Biodesign the process of innovating medical technologies - Zenios, Stefanos [ed.]; Makower, Josh [ed.]; Yock, Paul [ed.] (Cambridge Cambridge University Press, 2010)
master the design process, and develop business acumen with this 'how-to' guide to medical technology innovation. A three-step, proven approach to the biodesign innovation process - identify, invent, implement - provides a practical formula for innovation. The experiences of hundreds of innovators and companies, in the form of case studies, quotes and practical advice, offer a realistic, action-orientated roadmap for successful biodesign innovation. Real-world examples, end-of-chapter projects, and Getting Started sections guide the reader through each of the key stages of the process and provide a template to create their own new medical devices. Addressing common medical, engineering, and business challenges to develop well-rounded expertise, this book is the complete package for any biodesign entrepreneur. The text is supported by valuable resources, including up-to-date industry changes: found at ebiodesign.org.
Keywords: Biomedical engineering